O Conceito De Vida Nua Em Giorgio Agamben Uma Leitura Pelo Viés Dos Direitos Humanos - Santos, Bruno Barbosa Dos [UNIFESP] (2018)
The Following Research Intends To Analyze The Development Of The Concept Of Bare Life Described On Giorgio Agamben"S Works. Thus, We Will Return To The Textual References Used On The Conceptual Construction Of Homo Sacer Series, Likewise The Biopolitical Interpretation That The Author Realizes About Human Rights. Despite The Theme Of Human Rights Being A Marginal Matter On The Works Of The Italian Philosopher, We Found In Them A Privileged Field To Investigate The Political Status Of The Natural Life. We Consider, For Example, The Importance Of Categories Life And Human On The Philosophical Theories From Modern Age, Principally, Reassembling Them From The Natural Rights Tradition Until The History Of French Revolution. Then, Prompting The Biopolitical Debate About The Natural Life, We Will Question The Concept Of Humanity Prescribed By The Declarations Of Rights To Highlight The Emergency Of Bare Life Inside The Juridical Order Of National States. To This Extent, The Problem That Motivates The Research Is To